Factors Associated with Multiple Sexual Partnerships among Young Women in Southern African Countries: A Pooled Multilevel Analysis - Stephina Kgomotso Mbele (Advances in Public Health)
Background. Multiple sexual partnerships are one of the sexual behaviors that predispose young women to different negative outcomes, including sexually transmitted infections (STIs). This study aimed to examine the factors associated with multiple sexual partnerships among young women in selected Southern African countries. Materials and Methods. This study used cross-sectional secondary data from the Demographic and Health Surveys of six countries in southern Africa (Lesotho, Namibia, Malawi, South Africa, Zambia, and Zimbabwe). The data were collected using probability sampling (with a stratified two-stage cluster design) and structured questionnaires. This study used a weighted sample of 29,348 young women aged 15–24 years. The study included univariate, bivariate, and multilevel logistic regression (MLR) analysis. Moreover, a two-level model was used to measure the relationship between the selected explanatory factors and multiple sexual partnerships. Results. The overall prevalence of multiple sexual partnerships was 2.2% for the selected countries, and it differed by country. The factors associated with multiple sexual partnerships were age, marital status, educational level, employment status, having an STI, non-condom use, age at first sex, sex of the household head, and type of residence. The findings showed some variation in multiple sexual partnerships across communities. The findings from the MLR revealed that multiple sexual partnerships were high among women who were never married, no longer married, women with lower levels of education, and women who were employed. Moreover, higher odds of multiple sexual partnerships were found among women who had an STI, women from rich households, and women residing in Lesotho and South Africa. Conclusion. The study revealed that young women’s multiple sexual partnerships in Southern Africa are influenced by various sociodemographic factors. The study’s findings suggest a need for educational programs that focus on sexual health and economic empowerment, especially among unmarried and less educated women, thus reducing the associated risks and enhancing wellbeing.